PENGARUH ASPEK PENGUKURAN KINERJA DALAM BALANCED SCORECARD TERHADAP DAYA SAING PERUSAHAAN PDAM KOTA MAKASSAR - Husain, Rifkhi Anugrah; Pura, Rahman (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
The purpose of this research is examine the effect or measuring the performance of PDAM Makassar City on competitiveness in terms of financial and non-finacial performace using the Balanced Scorecard approach through four perspectives: financial, customer, internal business, and growth and learning. This research uses a quantitative approach and is a type of explanatory research. The sample used in this study was 20 employes and 20 customers of PDAM Makassar City. To test the hypothesis, multiple linear analysis was tested using SPSS version 22.00. The results of this study indicate that there is a significant positive relationship between in the Balanced Scorecard on the competitiveness of PDAM Makassar City.